Cross-Border Asset Holdings and Comovements in Sovereign Bond Markets - Hossein Asgharian; Lu Liu; Marcus Larsson (Lund University, School of Economics and Management, Department of Economics, 2015)
We analyze the importance of different types of asset holdings for the interdependence of the yield curves in the EMU using a spatial VAR model. We find that the cross-border holdings of long-term debt and bank lending are important for the interdependence. Our analysis of cross-sectional dispersion in sovereign-CDS-premium term structure shows that the differential in sovereign creditworthiness in the EMU is a main driver of the yield-curve divergence after 2008. The degree to which EMU countries' yield-curve slopes depend on the US slope decreases in the recent US recession, reflecting expectations during this period about future divergence of the US and EMU economies.
Keywords: C31; E43; G15; 330; yield-curve factors; cross-border asset holding; spatial dependence; EMU; sovereign credit default swap